Ownership concentration, board characteristics and firm performance. Issue 5 (15th June 2015) - Gaur, Sanjaya S.; Bathula, Hanoku; Singh, Deeksha
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to advance the understanding of the relationship between firm-level governance mechanisms and firm performance using a contingency framework. The contingency framework is based on an integration of agency theory, stewardship theory, resource dependence theory and stakeholder theory of firm governance. Design/methodology/approach – The authors test the arguments on a sample of all the listed firms on the New Zealand Stock Exchange between 2004 and 2007. Given the longitudinal nature of the data, the authors employ random effects, generalized least square estimation to run the regression models. Findings – The authors find that the presence of internal directors, CEO duality, board size and presence of professional directors leads to superior firm performance. A lack of ownership concentration leads to agency problems resulting in inferior performance. However, the positive effect of board independence on firm performance reduces in firms that have a high-ownership concentration. Additionally, a high-ownership concentration attenuates the positive effects of board size and board competence. Originality/value – This study helps reconcile some of the conflicting findings on firm governance-performance relationship. As the findings suggest, the effectiveness of a particular governance mechanism (such as board members) may depend on the presence or absence of another governance mechanism (such as ownership concentration). The integrative, multi-theoretic model that the authors propose in this paper is a unique contribution to the governance literature.